Women and occupational diseases in the European Union - Tieves, Daniela (Brussels, 2011)
"Daniela Tieves' report builds on a body of work done by our institute on the link between the struggle for equality and health at work. It draws on information gleaned through a network of contacts in a selected group of EU countries. It has the virtue of examining a set of national and European data on the impact of work on health through the filter of a gender perspective, highlighting the scale of discrimination in this area and offering useful insights both for policy makers and research."